Indole-3-Glyoxylamide- An Important Scaffold for Anticancer Activity - Buvana, C.; Raveendran, Avinash; Suresh, R.; Haribabu, Y. (Asian Journal of Pharmaceutical Research and Development, 2020)
Synthetic indolylglyoxyl amides were identified as a new group of microtubule destabilizing anticancer agents, with the most active derivative N-(pyridine-4-yl)-[1-(4-chlorobenzyl)indol-3-yl]glyoxylamide (Indibulin, D-24851, ) possessing the promising in vitro activity against SKOV3 ovarian cancer, U87 glioblastoma and ASPC-1 pancreatic cancer cells. Indole-3-glyoxylamides are an attractive lead series for continuing development as potential therapeutic agents. A number of Indole-3-glyoxylamides have previously been reported as tubulin polymerization inhibitors; exert a cytotoxic effect against multiple cancer cell lines. Recently, substituted indolylglyoxylamides were found to exhibit anticancer, antiprion and anti HIV activity. This developed an interest in reviewing lead based on indole-3-glyoxylamide. This review focused on overview of drug molecule of indole-3-glyoxylamide. We hope that the review could give a guide to develop newer anti-cancer agents with greater potency against drug-sensitive and drug-resistant cancers in the future.